2005
DOI: 10.1007/s10450-005-5901-z
|View full text |Cite
|
Sign up to set email alerts
|

Do the Differential Enthalpies of Adsorption Vary Between 77 K and 302 K? An Experimental Case Study of Argon and Nitrogen on Two Faujasite Type Zeolites

Abstract: Adsorption microcalorimetry of non-polar argon and quadrupolar nitrogen gases was carried out at 77 K and 302 K on two chemically different faujasite type zeolites (DAY and NaX). Considering absolute quantities adsorbed, the differential enthalpies of adsorption at zero coverage obtained with each system do not vary with temperature. Similarities in the differential enthalpies with increasing coverage are observed only if one considers non-specific adsorption phenomena either with a non-polar probe or on a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…17 The sample was activated by heating to 150 °C under secondary vacuum (<1 Â 10 À3 mbar). The apparent BrunauerÀEmmettÀTeller (BET) surface area was determined by adsorption of N 2 at 77 K in the relative pressure range of P/P 0 = 0.0002À0.01, following the guidelines proposed by Rouquerol et al 30 The sample was found to have a surface area of 1628 m 2 /g and a pore volume of 0.64 cm 3 /g. These values are among the highest reported in the literature and are very close to the values reported by Chang et al 17 for CuBTC prepared by microwave synthesis (1656 m 2 /g).…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…17 The sample was activated by heating to 150 °C under secondary vacuum (<1 Â 10 À3 mbar). The apparent BrunauerÀEmmettÀTeller (BET) surface area was determined by adsorption of N 2 at 77 K in the relative pressure range of P/P 0 = 0.0002À0.01, following the guidelines proposed by Rouquerol et al 30 The sample was found to have a surface area of 1628 m 2 /g and a pore volume of 0.64 cm 3 /g. These values are among the highest reported in the literature and are very close to the values reported by Chang et al 17 for CuBTC prepared by microwave synthesis (1656 m 2 /g).…”
Section: ' Materials and Methodsmentioning
confidence: 99%
“…Although it is not implicit in the thermodynamic definition of the isosteric heat of adsorption, it is often assumed that this quantity is at least approximately independent of temperature. Numerous experimental studies, performed mostly on conventional heterogeneous adsorbents such as silicas, zeolites, and carbons, confirmed that the isosteres of adsorption are linear in a wide range of temperatures, and therefore the isosteric heats of adsorption can be assumed to be temperature-independent. ,,, Only a few papers discuss the temperature dependence of the isosteric heats of adsorption. ,,,, Barrer and Stuart were perhaps the first to note considerable temperature dependence for heats of N 2 adsorption on Faujasite zeolites . Huang presented the T -dependence of Q st for N 2 in zeolites LiX, NaX, KX, and amorphous silica-alumina .…”
Section: Introductionmentioning
confidence: 99%
“…In determining the isosteric heat of adsorption from experimental data, eq is typically applied to several isotherms measured at different temperatures. In certain cases, calculations from a single experimental isotherm is possible, if an accurate model is available to predict isotherms at other temperatures . Calorimetry is used for direct measurements. , When a molecular model is available for an adsorbent, the isosteric heat of adsorption can be computed directly from molecular simulations. The isosteric heat of adsorption is important in detailed design of adsorption beds, as variations in bed temperature lead to changes in adsorption equilibrium. The isosteric heat of adsorption is also a useful proxy for adsorption selectivity in considering a range of materials for a separation of interest. ,, …”
Section: Introductionmentioning
confidence: 99%
“…26 The sample was activated by heating to 150 °C under secondary vacuum (<1.10−3 mbar). Apparent BET surface area was determined by adsorption of N 2 at 77 K in the relative pressure range P/P 0 = 0.0002−0.01, following the guidelines proposed by Rouquerol et al 27 The sample was found to have a surface area of 1628 m 2 /g and a pore volume of 0.64 cm 3 /g. These values are among the highest reported in the literature and are very close to the values reported by Chang et al 26 for CuBTC prepared by microwave synthesis (1656 m 2 /g).…”
Section: ■ Introductionmentioning
confidence: 99%